Analysis of Farmers' Knowledge and Attitudes Toward Foot and Mouth Disease in Langkat Regency - Ruth Dameria Haloho; Suci Andanawari; Adli Putra Ermanda; Irma Susanti; Nita Adillah Pratiwi; Fauzul Azhimah; Kiagus Muhammad Zain Basriwijaya; Dinar Anindyasari (Animal Science Study Program, Faculty of Agriculture, Science and Health, Universitas Timor, 2025)
The entry of FMD (Foot and Mouth Disease) into Indonesia occurs due to the import of meat from countries that are not yet free from the FMD outbreak. Increasing the knowledge of farmers is a way to address foot-and-mouth disease. This study aims to determine the level of education and attitudes of farmers towards foot-and-mouth disease. The research method is a survey study. The respondents are beef cattle farmers. Data analysis used quantitative descriptive analysis with a Likert scale. The research results show that The farmers are in their productive age, with most having completed senior high school education and having more than 18 years of livestock farming experience. The level of knowledge among farmers falls into the good category, meaning they are knowledgeable, and the farmers' attitude towards foot-and-mouth disease is agreeable in handling the disease.